“Quem procura trabalho não pode encontrar escravidão”: o combate à escravidão rural contemporânea no Brasil - Trindade, Solange de Moura (Universidade do Vale do Rio dos Sinos, 2013)
The present study has as its central theme the contemporary rural slave labor in Brazil, mode of exploration work recognized by OIT as Forced Labor, characterized by debt slavery. Emphasis will identification, description and questioning the actions of the federal government, with particular emphasis on the role of the MTE and Furniture Special Groups which, in national legislation, have the task of fighting and repression of contemporary slave labor. In methodological terms, we use the assumptions of bibliographic and documentary search, based in national and international legislation, as well as the data provided by the Federal Government, CPT, OIT, among others. We will use yet, as secondary source, data drawn from studies on the profile of enslaved worker and those who use slave labor. It is worth noting that the contemporary rural slavery in Brazil is closely linked with production arrangements typical of a strong technological development that uses, albeit peripheral, forced labor populations characterized by a strong social and economic vulnerability, that potentiate their recruitment. To perform work activities that thingify workers in flagrant violation of human rights.
Keywords: Trabalho escravo rural contemporâneo; Escravidão por dívida; Trabalho; Direitos humanos; Slave labor contemporary rural; Debt slavery; Labor; Human rights; ACCNPQ::Ciências Humanas::Sociologia